Incidence and factors associated with the risk of sexually transmitted diseases in HIV‐infected people seen for care in Italy: data from the Icona Foundation cohort. Issue 7 (11th May 2015) - Cingolani, A; Zona, S; Girardi, E; Cozzi‐Lepri, A; Monno, L; Quiros Roldan, E; Guaraldi, G; Antinori, A; D'Arminio Monforte, A; Marcotullio, S; Community‐Oriented Study Group of the Icona Foundation Study Group
<x xml:space="preserve">Abstract</x> Objectives The aims of this study were to identify temporal trends in the incidence of sexually transmitted diseases (STDs) in a cohort of HIV‐infected people and to evaluate factors associated with the risk of a new STD diagnosis. Methods All HIV‐infected patients in the Icona Foundation Study cohort enrolled after 1998 were included in this study. STD incidence rates (IRs) were calculated and stratified by calendar period. Predictors of STDs were identified using a Poisson regression model with sandwich estimates for standard errors. Results Data for 9168 participants were analysed [median age 37.3 (range 18–81) years; 74% male; 30% men who have sex with men (MSM)]. Over 46 736 person‐years of follow‐up (PYFU), 996 episodes of STDs were observed [crude IR 21.3/1000 PYFU; 95% confidence interval (CI) 20.0–22.6/1000 PYFU]. In multivariable Poisson regression analysis, MSM [rate ratio (RR) 3.03; 95% CI 2.52–3.64 versus heterosexuals], calendar period (RR 1.67; 95% CI 1.42–1.97 for 2008–2012 versus 1998–2002), HIV RNA > 50 HIV‐1 RNA copies/mL (RR 1.44; 95% CI 1.19–1.74 versus HIV RNA ≤ 50 copies/mL) and a current CD4 count < 100 cells/μL (RR 4.66; 95% CI 3.69–5.89; P < 0.001 versus CD4 count > 500 cells/μL) were associated with an increased risk of STDs. In contrast, older age (RR 0.82 per 10 years older; 95% CI 0.77–0.89) and being currently on ART (RR 0.38; 95% CI 0.33–0.45) compared with being ART‐naïve or on a treatment interruption were associated with a lower risk of developing STDs. Conclusions An increase in the incidence of STDs was observed in more recent years. Interventions to prevent STDs and potential spread of HIV should target the younger population, MSM and people currently not receiving ART.